2020
DOI: 10.1001/jama.2020.13095
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Counseling Interventions to Prevent Sexually Transmitted Infections

Abstract: Bacterial and viral sexually transmitted infections (STIs) are common in the US. Approximately 20 million new cases of bacterial or viral STIs occur each year in the US, and about one-half of these cases occur in persons aged 15 to 24 years. 1,2 Rates of chlamydial, gonococcal, and syphilis infection continue to increase in all regions. 2 Sexually transmitted infections are frequently asymptomatic, which may delay diagnosis and treatment and lead persons to unknowingly transmit STIs to others. Serious conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…The results from this critical inquiry will further clarify the potential role for a joint health educator–administered sexual education and counseling intervention in enhancing AYA access to sexual and reproductive health services in primary care settings and will determine the feasibility, acceptability, and effectiveness of using the sexually involved dyad as a vehicle for behavioral change. It will also give us an insight into the role of actively engaging sexual partners in joint communications for promoting healthier sexual behaviors on STI prevention compared to the general practice of individualized risk reduction counseling, partner notification, and expedited therapy without mutual engagement [ 14 , 17 , 34 ]. Dyadic interventions have been used in many medical conditions including parent-adolescent dyads for improving HIV prevention and self-efficacy [ 35 ], obesity prevention, and smoking and sedentary lifestyle cessation and were influential for sparking behavior changes [ 36 ] and preventing HIV transmission between serodiscordant same-sex male couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this critical inquiry will further clarify the potential role for a joint health educator–administered sexual education and counseling intervention in enhancing AYA access to sexual and reproductive health services in primary care settings and will determine the feasibility, acceptability, and effectiveness of using the sexually involved dyad as a vehicle for behavioral change. It will also give us an insight into the role of actively engaging sexual partners in joint communications for promoting healthier sexual behaviors on STI prevention compared to the general practice of individualized risk reduction counseling, partner notification, and expedited therapy without mutual engagement [ 14 , 17 , 34 ]. Dyadic interventions have been used in many medical conditions including parent-adolescent dyads for improving HIV prevention and self-efficacy [ 35 ], obesity prevention, and smoking and sedentary lifestyle cessation and were influential for sparking behavior changes [ 36 ] and preventing HIV transmission between serodiscordant same-sex male couples.…”
Section: Discussionmentioning
confidence: 99%
“…In response to this public health failure, many states are establishing regulations to implement expedited partner therapy [ 14 - 16 ]. In addition, the US Preventive Task Force recently recommended the integration of behavioral counseling as part of STI management, especially for adolescents at higher risk for new or recurrent disease [ 17 ]. This clinical change is estimated to have a moderate benefit and will reduce the probability of acquiring new STIs.…”
Section: Introductionmentioning
confidence: 99%
“…The USPSTF has issued a separate recommendation for screening for syphilis infection in pregnant persons as well as screening recommendations for other STIs, including hepatitis B, hepatitis C, genital herpes, HIV, and chlamydia and gonorrhea . The USPSTF has also issued a recommendation on behavioral counseling for all sexually active adolescents and for adults who are at increased risk for STIs …”
Section: Practice Considerationsmentioning
confidence: 99%
“…Sexual histories during primary care visits provide important details to help guide testing, diagnosis, and treatment of STIs as well as an opportunity to offer prevention-focused behavioral counseling in accordance with the United State Preventive Services Task Force (USPSTF) guidelines. 5 , 6 A survey of 3,300 adults found that only one-quarter of patients reported being asked about sexual health or STIs by their primary care physicians during their last visit. 7 One unique issue in primary care STI screening is that patients with varying levels of STI risk are seen.…”
Section: Introductionmentioning
confidence: 99%